Efektivitas Warna Lampu Perangkap terhadap Imago Ulat Kantong (Mahosena corbetti) di Perkebunan Kelapa Sawit PTPN IV Tanah Raja - Sitorus, Andri Sulaiman; Azwana, Azwana (Universitas Medan Area, 2026)
The purpose of the study was to determine the effectiveness of the color of the trap light on the imago of bagworms (Mahosena corbetti) in the oil palm plantation of PTPN IV Tanah Raja. The study was conducted This study was conducted in the oil palm plantation at PTPN IV Tanah Raja which is located in two (2) sub-districts, namely Sei Rampah Sub-district and Teluk Mengkudu Sub-district, Serdang Berdagai Regency with a distance of ± 56 km from Medan city and ± 30 km from Tebing Tinggi which was carried out in Afdeling V in July - August 2024. The study is a type of quantitative descriptive research, namely by using survey and experimental methods. The results of the study show that the yellow light can catch 159 individuals/plot, the white light obtained the number of imago catches of 64 individuals/plot, while the use of green light color 0 individuals/plot. To see the difference in the number of bagworm imago catches, a t-test with two paired samples was carried out. The t-test results showed a t-value of 10.46 greater than the t-table of 2.78 with a significance value of 0.000 0.05, so the number of catches in the yellow light was significantly more than the white light. It can be concluded that yellow light can be used as an effective catcher in controlling the bagworm population in oil palm plantations.